Effect On Learners' Achievement of Using Language in Online Learning Environments - Atici, Bunyamin (Int Information Inst, 2011)
Whilst the information and communication technologies become more widespread, it changes students' form of language usage. It is a fact that there are changes in the usage of the language thru online training applications such as blogs, instant messaging (chat), and forums. It can even be said that during online applications the users have created their own language. This study addresses to the effects on the success of students' language usage patterns and their personal word power that participated face-to-face and online training applications as synchronously and asynchronously. Out of 90 students, who were participated to the study, 45 of them took the training synchronously and the other 45 took asynchronously. Words that students used in synchronous and asynchronous environments were processed with MaxQda, the qualitative data analysis program, and it has been determined the number of words that they were using as total and different words. According to the results obtained from the study, it has been detected that the students were expressing themselves with approx. 127 words in synchronous environments. It has been determined that students whom expressed themselves with above 60 words in this environment were more successful than the others. It has been determined that in the asynchronous environment, students used average 1146 words. Also in this environment it has been found out that the students, who were using above 600 words in average, are more successful. The comparison between students participated to synchronous and asynchronous environments there were no significant differences of their success.
Keywords: Online learning; word power; learning; language use